Apologia do fluxo, ou sobre o antropoceno no Rio Grande do Sul e a percepção da paisagem no rio Caí - Coelho, Caio Fernando Flores (2023)
At the 19 th Century’s end, São Sebastião do Caí developed as a haven on the last navigable stretch for medium-draft steamships of the Caí river. During the navigation period, this city was the main connection between Rio Branco road (which ran from the lower Caí valley to Caxias do Sul) and the Caí river waterway that followed to Porto Alegre. Over three centuries of peak and decline economic fluctuations, this city was constituted as a living space for the community on the left bank of the river. However, the coexistence between this community and the river did not run smoothly. This study proposes a historical analysis of the human-landscape relationship between the population inhabiting the Caí river and its surroundings. For this, we seek to understand the history of this river through the lens of the longue durée . Events (of short duration) and conjunctural periods that marked the history of the Caí population were identified, such as river navigation, the industrialization process, urban organization and economic decline. However, we find the city's floods as the main permanence structure in the continuous interaction between the river and its inhabitants. To carry out this analysis, the category of perception of the landscape was used, an adaptation of the concept of perception of the environment by Tim Ingold (2000), where the division between the natural world (of the given fact) and the (imaginary) cultural universe is tangential. In this way, the landscape is seen as a relational space built through human action on the environment. This relationship, however, takes place in aesthetic terms, based on the visual perception that makes sense of the horizon that surrounds us. In this attempt, several documentary, cartographic and imagery sources were used to deal with the way the river is perceived, used and modeled according to the regional economic needs. Therefore, this thesis is divided into three parts: the first contextualizes the Caí river and its region from the beginnings of European colonization to the beginning of its anthropocenic industrialization between the 17 th and 19 th centuries; the second analyzes the economic development of the city based on commercial navigation at the turn of the 19 th century and first decades of the 20 th century; and the third analyzes the reciprocity process of living with the river, dealing with the nature that resists human interventions, either by the floods, or by the cultivation of a local memory and identity that assert themselves of the presence and permanence of the Caí river,and the daily life of its waters between 1854 and 2020.